Beginning of Contemplation in Sight of St. John of the Cross and Ala Al-Dawla Semnani - Abdolkhalegh Jafari; Bakhshali Ghanbari; Abdolreza Mazaheri (Universitas Islam Negeri Mataram, 2021)
Contemplation is a central topic in the gnostic customs of Christianity and Islam. Christian and Islamic mystics, however, dissent on whether or not contemplation is a kind of position or an emotional mood. St. John of the Cross and Ala Al-Dawla Semnani are among the mystics of Christianity and Islam who have talked on contemplation, and comparison of views of these two can bring new sights on the subject. According to Ala Al-Dawla Semnani, disciples must strive to reach gnostic excellence by praising verbally and heartily. That is, the disciple must schedule praising around the clock and give all his or her attention to the God and heartily pray for the gloriousness of the exalted God. According to John of the Cross, however, one must keep going forward only and only by heeding the God without doing anything else. Both mystics have different views about how to enter the course of contemplation. Ala Al-Dawla Semnani has covered this topic by outlining more features and in a more transparent manner. But according to John of the Cross, entry to a course of contemplation is a vague experience of the God that we receive passively not as a result of our efforts.